O TEATRO DO PODER: Cultura e Política no Maranhão - CARDOSO, Letícia Conceição Martins (2008)
Analysis of the cultural management of the governments of Roseana Sarney in Maranhão (1995-1998/1999-2001), designed by Maranhão Culture Secretary (SECMA) and Maranhão Culture Foundation (FUNCMA). It s searched to identify the field of cultural relations between actors and the State, taking as reference the speeches of those actors through interviews, analysis of the Activities Reports of SECMA/FUNCMA and reports in local newspapers. The Government of Roseana Sarney is located on the discussion of culture public policy in Brazil and a study about the culture state policies in the country which manufactured national symbols until José Sarney government as President of Brazil (1985 -1980), when was created the first Law of the Encouragement Culture (Sarney Law). It s observed that in the first time of the cultural management of Roseana Sarney (1995- 1997) a conception of culture identified with the heritage was predominated. And, in a second time (1998-2001), state interventions focused on a concept of popular culture . In both moments theatrical strategies are created, leading to a symbolic capital accumulation on the protagonist: the governor. But the cultural actors are active subjects in this play, also creating their visibility strategies. Thus, power dispute is developed through stage of power acts. In this context, the media is an important scene for the acquisition of symbolic power and can serve both as a group or another. The intention, therefore, is to explain how the relations between the State and culture are established; to know what strategies are used, why and by whom are developed, trying to identify if these relations can be considered a public policy of culture.